2016
DOI: 10.1111/echo.13172
|View full text |Cite
|
Sign up to set email alerts
|

Thrombus‐in‐Transit Following Watchman Device Implantation

Abstract: Thrombus-in-transit crossing an interatrial communication is a rare but potentially serious clinical condition, which has so far not been described after implantation of left atrial appendage (LAA) closure devices. Here, we describe the case of a 76-year-old woman with permanent atrial fibrillation and contraindication for oral anticoagulation therapy, who developed pericardial tamponade and acute pulmonary embolism with visible thrombus-in-transit formation following LAA closure. Most likely manipulation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Large sheaths and longer procedural times are the main risk factors for the formation of deep venous thrombosis. 12) Wallenborn, et al 13) have reported a case of postoperative thrombus-in-transit originating from deep vein thrombosis, which led to pulmonary embolism, and they have advised vigilance to the occurrence of such incidents after LAAC, particularly when using large bore introducers during the surgery. To the best of our knowledge, thrombi adhering to the puncture site of the right atrial septum formed during LAAC without causing severe thromboembolic events are rarely reported, and this may be the first such case to be reported.…”
Section: Discussionmentioning
confidence: 99%
“…Large sheaths and longer procedural times are the main risk factors for the formation of deep venous thrombosis. 12) Wallenborn, et al 13) have reported a case of postoperative thrombus-in-transit originating from deep vein thrombosis, which led to pulmonary embolism, and they have advised vigilance to the occurrence of such incidents after LAAC, particularly when using large bore introducers during the surgery. To the best of our knowledge, thrombi adhering to the puncture site of the right atrial septum formed during LAAC without causing severe thromboembolic events are rarely reported, and this may be the first such case to be reported.…”
Section: Discussionmentioning
confidence: 99%